Therapeutic Potential of Glycosyl Flavonoids as Anti-Coronaviral Agents - Patrícia I. C. Godinho; Raquel G. Soengas; Vera L. M. Silva (MDPI AG, 2021)
The COVID-19 pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread all over the world, creating a devastating socio-economic impact. Even though protective vaccines are starting to be administered, an effective antiviral agent for the prevention and treatment of COVID-19 is not available yet. Moreover, since new and deadly CoVs can emerge at any time with the potential of becoming pandemics, the development of therapeutic agents against potentially deadly CoVs is a research area of much current interest. In the search for anti-coronaviral drugs, researchers soon turned their heads towards glycosylated flavonoids. Glycosyl flavonoids, widespread in the plant kingdom, have received a lot of attention due to their widely recognized antioxidant, anti-inflammatory, neuroprotective, anticarcinogenic, antidiabetic, antimicrobial, and antiviral properties together with their capacity to modulate key cellular functions. The wide range of biological activities displayed by glycosyl flavonoids, along with their low toxicity, make them ideal candidates for drug development. In this review, we examine and discuss the up-to-date developments on glycosyl flavonoids as evidence-based natural sources of antivirals against coronaviruses and their potential role in the management of COVID-19.